On ordered G-semihypergroups Containing Two-sided Bases - Jantanan, Wichayaporn; Budpan, Chanon; Loesna, Weeradon (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 3 (2021): July-September 2021DO - 10.14456/nujst.2021.29, 2021)
The main purpose of this paper is to study the concept of an ordered G-semihypergroup containing two-sided bases that are studied analogously to the concept of G-semigroup containing two-sided bases considered by Thawhat Changpas and Pisit Kummoon in 2018. We introduce the notion of an ordered -semihypergroup containing two-sided bases and describe some property of an ordered G-semihypergroup containing two-sided bases.